Stock Returns and Economically Neutral Behavioural Variables: Evidence from the Nepalese Stock Market - Bhattarai, Ram Chandra; Joshi, Nayan Krishna (NRB Economic Review, 2007)
This article investigates whether or not the Nepalese stock market is efficient in weak form with respect to economically neutral behavioural variables. Simple OLS technique with White’s heteroskedasticity-corrected standard errors is used to test the relationship between stock returns and economically neutral behavioural variables represented by weather (cloud cover and temperature) and biorhythms (seasonal affective disorder). The findings indicate the existence of weak-form efficiency in the market for “temperature” and “seasonal affective disorder” but not for the “cloud cover”. These findings are not consistent to those of results documented for developed and emerging stock markets.